(untitled) (Journal of Economic Research & Business Administration, 2016)
The article discusses the technique of investing in stocks, namely, what indicators to consider when investing in this instrument. As the object of the analysis were used trading platforms NYSE and NASDAQ. The main indicators have been proposed stock index, the market capitalization of the company, the rate of earnings per share and beta coefficient. The last factor will help the investor to predict the level of risk of a particular stock. High dynamics of development of the stock market makes it necessary to find new and effective management practices. The method of analysis of market indicators will serve as a reference point in the direction of the market and the stock assessment. After all, the forecast growth rate or falling action is not always possible to predict with accuracy. It’s no secret, the emergence of rating agencies help investors and professional participants in the selection of issuers of debt securities. Therefore, the publication of the values of “beta” factor also gives investors more advantages in investing in shares. Comparing the values of the indicators, the investor share comfortably to rank level of risk and select an action in accordance with the wishes of investors.